Strategi Komunikasi dalam Pengembangan Desa Agro Wisata di Desa Manggala Lombok Utara - Sayu Kadek Jelantik; Rieka Yulita Widaswara; I Ketut Putu Suardana; Ni Putu Sasmika Dewi; Ni Nyoman Harnika; Ida Kade Suparta; I Kadek Dwi Jendra Panida (Dharma Sevanam : Jurnal Pengabdian Masyarakat, 2023)
The IAHN Gde Pudja Mataram Cultural and Religious Tourism Study Program is located in Manggala Village, North Lombok in 2022. This community service activity aims to provide training in developing the agro-tourism village they have. Attraction Manggala Village, which is in the middle of the Pusuk forest, is an agro-tourism area that has a special place in the hearts of tourists. The agro-tourism potential developed in Manggala Village, North Lombok Regency, utilizes natural resources and typical mountain plantations to be excellent in Manggala Village to be better developed into an agro-tourism village so that the implementation of an effective communication strategy with the media and utilizes the human resources involved in it. This research was conducted to examine communication strategies in the development of agro-tourism villages in Manggala Village, North Lombok. The purpose of this research is to analyze the communication strategy process for developing agro-tourism villages in Manggala Village, North Lombok. The method used in this research is descriptive qualitative with an expose facto approach and uses observation, interview, and documentation techniques to collect data. The results of research conducted in the community service program Undergraduate Cultural and Religious Tourism Study Program provide counseling on human resource development materials and Agro-tourism products and training on packaging agro-tourism products through digital media by conceptualizing plantation activities and products in the form of spices, sugar palm cultivation, and bamboo as well as training on the packaging of natural and cultural tourism products where there is an important element in the communication strategy process, namely the existence of communicators, namely the community and government as the driving force in developing an agro-tourism village in Manggala Village, North Lombok. The second element is the message that is conceptualized in the form of verbal and non-verbal messages that contain ideas that are collaborated with noble values ​​that exist in the community of Manggala Village, North Lombok, for example reading materials for planting types of plants that have economic value. The third element is the media used to package messages for agro-tourism products with digital media. The fourth element is shooting prospective tourists with clear targets so that the communication strategy implemented can work effectively.